Assessment and comparison of laparoscopic hernia repair versus open hernia: a non-randomized study - Murthy, P. Krishna; Ravalia, Dilip (International Surgery Journal, 2018)
Background: Hernia is the abnormal exit of an organ or fatty tissue, such as the bowel, through the wall of the cavity in which it normally resides. Repair of inguinal hernia is one of the common surgical procedures done worldwide. Present study was performed with an aim to compare the effectiveness of laparoscopic hernia repair and Lichtenstein’s hernioplasty and to know for any special pre-operative/ intra operative requirements for surgery. Methods: Present study is a non-randomized comparative study. The study consisted 50 patients treated with Hernioplasty (20 cases of laparoscopic hernioplasty and 30 cases of open hernioplasty in the Department of General Surgery, during the study period of one year. Data were collected using a questionnaire. Results: Mean operating time in group A was 92.25 minutes while in group B was 43.5 minutes, which is significantly supplementary. Pain score was significantly less in group A with 75% patients giving score 1-2 (mild pain) and 3 patients with discomforting pain with p<0.05. Conclusions: laparoscopic pre-peritoneal mesh repair of inguinal hernia is safe and efficacious and offers definitive advantages over open mesh repair and should be an available option for all patients requiring elective Hernioplasty.